Correlation of Morphometric Variables for Landslides in the Combeima River Basin, Colombia (2020)
This study was carried out in order to estimate the morphometric variables of the landslides found in Combeima river basin (Tolima, Colombia) and obtain possible statistical correlations. To obtain the morphometric characteristics of the landslides, we used a database with historical landslides, a RapidEye image from 2010 and an orthophotomosaic from 2009, where the landslides were visually identified. The morphometric characteristics were defined through a geographic information system and bivariate analyzes were ran between the morphometric variables to establish their correlations. The results allowed to identify 121 landslides, with an average area of 1,974.97 m2 and Birnbaum-Saunders type distribution. It was found that the slip area morphometric variable correlates with the total length (R2=0.9414), the length of the center line (R2=0.9368) and the width of the surface of rupture of this (R2=0.8915). These data could be used to infer the volume of the mass involved in the event and its potential effects . This result would allow the landslide area to be used as support in decision-making in the planning of the territory in the Combeima river basin.